The Influence of Belief Consumers on Product Purchasing Decisions Beauty Online Through E -Commerce - Mulyani Rizki; Tanti Rosa Diyan Pratiwi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The development of trade in Indonesia has experienced a rapid increase, especially in the fashion and accessories trade business. Indonesian Muslim society today is increasingly aware of the importance of fashion aspects that not only involve choosing clothes, but also relate to style and trends, even when they wear the hijab. The high intensity of Muslim fashion purchases through e-commerce in recent years and how important it is to meet lifestyle needs without forgetting one's religious identity. Judging from the above phenomenon, researchers are interested in exploring and assessing the impact of consumer trust on online beauty product purchasing decisions through E-Commerce. The purpose of this study is to determine how consumer trust influences online beauty product purchasing decisions through E-Commerce. The number of samples in this study was 100 respondents, this study used a quantitative approach. The data collection technique in this study used a questionnaire, and the sampling technique used a simple random sampling method. The data obtained were then processed using the SPSS 26 application. Based on the results of the study, it shows that Trust has a positive and significant effect on online beauty product purchasing decisions through e-commerce. Proving that ha is accepted, the results of this study indicate that high trust can influence consumers to make purchases through e-commerce.